2010
DOI: 10.1590/s0100-736x2010000900004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de anticorpos anti-Neospora caninum (Apicomplexa: Sarcocystidae) em bovinos leiteiros de propriedades rurais em três microrregiões no estado do Maranhão

Abstract: Objetivou-se, no presente estudo, pesquisar a prevalência de anticorpos anti-Neospora caninum em 812 amostras de soros sangüíneos de bovinos leiteiros procedentes de propriedades rurais de sete municípios das microrregiões de Itapecuru-Mirim, Médio Mearim e Presidente Dutra, estado do Maranhão, Brasil. Para o cálculo do tamanho da amostra, considerou-se um soroprevalência de 34,7% para N. caninum, com erro máximo de 9,5% e intervalo de confiança de 95%. Para a detecção da presença de anticorpos da classe IgG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
(31 reference statements)
3
15
1
6
Order By: Relevance
“…Higher frequencies as 62,90%, 40,91%, and 50,74% were determined by Belo et al (1999), Silva et al (2010), and Teixeira et al (2010), respectively, at a cutoff at 1:200, in six dairy herds with a history of miscarriage in the northeastern region of São Paulo, in buffaloes and dairy cattle from 13 municipalities in Pará, and in three microregions of the state of Maranhão. Sartor et al (2005) obtained higher frequencies of 35,54% and 20,00%, respectively, in dairy and beef cattle in Presidente Prudente, SP, by using ELISA.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Higher frequencies as 62,90%, 40,91%, and 50,74% were determined by Belo et al (1999), Silva et al (2010), and Teixeira et al (2010), respectively, at a cutoff at 1:200, in six dairy herds with a history of miscarriage in the northeastern region of São Paulo, in buffaloes and dairy cattle from 13 municipalities in Pará, and in three microregions of the state of Maranhão. Sartor et al (2005) obtained higher frequencies of 35,54% and 20,00%, respectively, in dairy and beef cattle in Presidente Prudente, SP, by using ELISA.…”
Section: Resultsmentioning
confidence: 80%
“…On the other hand, Teixeira et al (2010) obtained 32,04% in dairy cattle from three micro-regions in the state of Maranhão in 400 titer. In buffaloes reared in Pará, 46,04% of the positive sera were in the ≥800 titer, while 46,51% of goat sera from the southern region of Minas Gerais were in 50 titer VARASCHIN et al, 2011). In cattle reared in Santarém, Pará, the largest number of positive samples, 33,30%, was in the 200 titer (MINERVINO et al, 2007).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…As reported for goats (Eleni et al 2004), clinical cases associated to natural infection of sheep by Neospora caninum are uncommon, with a few abortion cases , Jolley et al 1999) and congenital disorders (Pena et al 2007) described. However, several serological surveys conducted in different countries, including Brazil, showed that the infection is disseminated in this species (Figliuolo et al 2004, Salaberry et al 2010, as well as in other animal species , Teixeira et al 2010, Toscan et al 2010, Camillo et al 2011, Varaschin et al 2011. In cattle, abortions caused by N. caninum are common (Corbelliniet al 2000, Pescadoret al 2005, Oliveiraet al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, as in cattle farming, they may be related to abortion, reduction in animal value, increase in interparturition interval, infertility and decrease in milk production (Trees et al 1999). Neosporosis in Brazil was detected in many animal species (Toscan et al 2010, Teixeira et al 2010,Camillo et al 2011, Varaschin et al 2011), but its association to abortion was found only for cattle (Gondim et al 1999, Corbellini et al 2000, Corbellini 2001, Pescador et al 2007). In an attempt at ϐilling this gap, the present study aims to describe sheep abortions caused by N. caninum in the state of Mato Grosso do Sul, Brazil.…”
Section: Introductionmentioning
confidence: 99%